(untitled) (Mongolian Journal of Chemistry, 2024)
This study utilized featherback skin to generate a versatile protein hydrolysate having capacities of iron chelation, emulsification, foaming and amino acid supplement. The hydrolysate obtained under the chosen condition (Alcalase, the skin:water ratio of 1:9 (w/v), pH 7.5, 55°C, enzyme:substrate (E:S) ratio of 40 U/g protein, 4 h of hydrolysis) showed an iron-binding capacity (IBC) of 7085.2 ± 4.2 (μg Fe2+/g protein), being equivalent to that of ethylenediaminetetraacetic acid disodium salt (Na2EDTA). Together with a high content of hydrophobic amino acids (63.34 mg/L), in the pH range 3-8, the emulsifying property of the hydrolysate was remarkable with emulsifying activity index (EAI) of 0.16-0.21 m2/g protein and emulsifying stability index (ESI) of 35.1-107.1 min, which were 1.7- 2.3 folds lower and 1.6-5.0 folds higher than those of sodium caseinate, respectively. Meanwhile, the hydrolysate exhibited mild foaming property with its foaming capacity (FC) and foaming stability (FS) being 3.6-16.6 folds lower than those of albumin.